ELECTROCONVULSIVE THERAPY (ECT) FOR THE MANAGEMENT OF NEUROLEPTIC MALIGNANT SYNDROME (NMS) IN ADULTS: Neuroleptic Malignant Syndrome - Raja, Waseem; Liaqat, Jahanzeb; Javed, Muhammad Umar; Naseem, Arshad; Wali, Waseem (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the efficacy and safety of electroconvulsive therapy (ECT) for the management of neuroleptic malignant syndrome (NMS) in adults. Study Design: Open label, unblinded series. Place and Duration of Study: This study was carried out at the Department of Neurology, Military Hospital Rawalpindi, from Jan 2015 to Dec 2015. Material and Methods: All the patients with the diagnosis of NMS during the study period were included in the study. Consective non-probability sampling technique was used. Patients were divided into two groups; uncomplicated and complicated cases of NMS. Results: A total of nineteen patients were included in this pilot study. Out of all, thirteen (68.4%) were males and six (31.6%) were females. Mean age of the patients was 35.05 (SD 13.362) years. The drug classes causing NMS were antipsychotic medicines in 73.7% of patients and antiemetics in 26.3% of patients. Mean electroconvulsive therapy (ECT) sessions given were 6.16 (SD 2.062). Following treatment n=16 (84.2%) patients had complete recovery while n=3 (15.3%) patients died. Conclusion: In this small, open label, unblinded study ECT appears effective and safe in treating NMS in adults. Larger randomized studies will help to confirm data emerging from this preliminary study.